Morphological characteristics and habitat conditions of suweg (Amorphophallus paeoniifolius) around Mount Ciremai National Park, West Java, Indonesia - ASEP ZAINAL MUTAQIN; DENNY KURNIADIE; JOHAN ISKANDAR; MOHAMAD NURZAMAN; TEGUH HUSODO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mutaqin AZ, Kurniadie D, Iskandar J, Nurzaman M, Husodo T. 2021. Morphological characteristics and habitat conditions of suweg (Amorphophallus paeoniifolius) around Mount Ciremai National Park, West Java, Indonesia. Biodiversitas 22: 2591-2600. Indonesia is a country that has abundant biodiversity, especially the diversity of plant species. One of the plant species that widely distributed across Indonesia is Amorphophallus paeoniifolius (Dennst.) Nicolson, or locally known as suweg. This study aims to identify morphological characteristics of A. paeoniifolius and its habitat conditions around Mount Ciremai National Park, West Java Province, Indonesia. Several stages of the exploratory survey were randomly carried out followed by purposive intensive observations. The method used to collect and analyze data is qualitative methods combined with simple measurements of quantitative technique. The results showed that suweg in the studied areas had distinctive morphological characteristics, which are different from the rest of the species from Amorphophallus genus. The plant is found in 4 types of land, namely home gardens, gardens, rice fields, and pond edges, whether with open or closed canopy conditions. The density of suweg in the study area is generally low. The climatic and edaphic conditions of suweg habitat in several study areas showed that there are a lot of similarities of conditions with other references. There are also 156 species of plants found that grow around suweg, both in the category of cultivated and wild plants. This- study enriches the existing knowledge on the botanical and ecological information of A. paeoniifolius in the context of geographical area (i.e., Ciremai National Park, West Java, Indonesia).